Silk fibroin/polymer hybrid nanoparticles as a potential treatment for hair split-ends - Duy Toan Pham, Bao Chau Nguyen, Hien Triet Nguyen, Ngoc Yen Nguyen, Ngoc Huyen Nguyen, Waree Tiyaboonchai (Journal of Applied Pharmaceutical Science, 2025)
Current treatments for hair split-ends are the hair care leave-on cosmetics such as conditioners and serums containing silicones and/or quaternium compounds, which possess potential skin irritation, inadequate efficacy, and short duration of action. Thus, this research developed novel leave-on natural products from silk fibroin/ polymer hybrid nanoparticles (FNP and FNP/polymer) for the treatment of hair split-ends. Using cosmeceutical polymers of poly(ethylenimine) (PEI), poly(vinyl pyrrolidone) K30 (PVP K30), poly(vinyl alcohol) (PVA), and poly(ethylene glycol) 400 (PEG 400), a total of five formula was prepared by the simple one-pot desolvation process, including FNP, fibroin, and PEI hybrid nanoparticles (FNP/PEI), fibroin and PVP K30 hybrid nanoparticles, fibroin and PVA hybrid nanoparticles, and fibroin and PEG 400 hybrid nanoparticles. All formulas showed favorable physicochemical properties for a leave-on hair care product, namely nano-sizes of 151.3–338.6 nm, adjustable zeta potentials (+55 mV for FNP/PEI and −25 mV for others), dominant silk-I structures, and non-irritation property. Significantly, compared to the commercial product, which only restores the split-ends for 1.5 hours, all nanoparticle aqueous dispersions could re-bind the split-ends hair fibers back to their original shape for more than 72 hours, without any support from other cosmeceutical excipients. Conclusively, the FNP and FNP/polymer hybrid systems could become a potential natural hair leave-on cosmetic for the treatment of hair split-ends.
Keywords: Fibroin, nanoparticles, polymers, formulation/ stability, hair treatment, split-ends